Pengabdian masyarakat dalam membantu pembuatan laporan keuangan Gereja di Surabaya - Evelyn, Evelyn (LPPM IT Telkom Purwokerto, 2025)
This article aims to describe community service activities undertaken to assist in the preparation of financial statements at one of the GKI churches in Surabaya. It outlines the theoretical framework of church financial reporting, the benefits of financial statements for the Synod, Church, and congregation, and provides step-by-step instructions for creating Microsoft Excel templates tailored to the church's financial reporting needs. The methods employed in this community service include the creation and refinement of Microsoft Excel templates, communication and socialization with the church treasurer, and ongoing evaluation and improvement from 2018 to 2024. The results of these activities demonstrate increased efficiency and accuracy in the preparation of church financial statements, enhanced technical skills of the treasurer, and adherence to the principles of transparency and accountability in church fund management. This article aims to highlight the benefits of using Microsoft Excel for producing more accurate and efficient church financial statements